2019
DOI: 10.1093/tbm/ibz005
|View full text |Cite
|
Sign up to set email alerts
|

Advancing implementation frameworks with a mixed methods case study in child behavioral health

Abstract: Despite a growing policy push for the provision of services based on evidence, evidence-based treatments for children and youth with mental health challenges have poor uptake, yielding limited benefit. With a view to improving implementation in child behavioral health, we investigated a complementary implementation approach informed by three implementation frameworks in the context of implementing motivational interviewing in four child and youth behavioral health agencies: the Active Implementation Frameworks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…1 ), including: (1) a Usable Intervention; (2) Implementation Stages; (3) Implementation Teams; (4) Implementation Drivers; and (5) Quality Improvement Cycles ( Fixsen, Blase, Timbers, & Wolf, 2001 ; Fixsen, Naoom, Blase, Friedman, & Wallace, 2005 ; Fixsen, Blase, Metz, & Van Dyke, 2013 ; Metz & Bartley, 2012 ; Metz et al, 2015 ). Previous work indicates that implementation and evaluation efforts guided by the AIF have resulted in the effective translation of interventions to support practice change among providers in healthcare, social service, and education-based settings ( Barac, Kimber, Johnson, & Barwick, 2018 ; Barwick et al, 2019 ; Couturier et al, 2017 , 2018 ; Kimber, Barac, & Barwick, 2017 ; Kimber, Barwick, & Fearing, 2012 ; Metz et al, 2015 ; Romney, Israel, & Zlatevski, 2014 ; Saldana, Chamberlain, Wang, & Hendricks Brown, 2012 ; Velonis, O’Campo, Rodrigues, & Buhariwala, 2019 ).…”
Section: Overview Of the Researching The Impact Of Service Provider Ementioning
confidence: 99%
“…1 ), including: (1) a Usable Intervention; (2) Implementation Stages; (3) Implementation Teams; (4) Implementation Drivers; and (5) Quality Improvement Cycles ( Fixsen, Blase, Timbers, & Wolf, 2001 ; Fixsen, Naoom, Blase, Friedman, & Wallace, 2005 ; Fixsen, Blase, Metz, & Van Dyke, 2013 ; Metz & Bartley, 2012 ; Metz et al, 2015 ). Previous work indicates that implementation and evaluation efforts guided by the AIF have resulted in the effective translation of interventions to support practice change among providers in healthcare, social service, and education-based settings ( Barac, Kimber, Johnson, & Barwick, 2018 ; Barwick et al, 2019 ; Couturier et al, 2017 , 2018 ; Kimber, Barac, & Barwick, 2017 ; Kimber, Barwick, & Fearing, 2012 ; Metz et al, 2015 ; Romney, Israel, & Zlatevski, 2014 ; Saldana, Chamberlain, Wang, & Hendricks Brown, 2012 ; Velonis, O’Campo, Rodrigues, & Buhariwala, 2019 ).…”
Section: Overview Of the Researching The Impact Of Service Provider Ementioning
confidence: 99%
“…Therefore, when thinking of the most pragmatic and cost-e cient method of delity measurement, therapist rating would likely meet these requirements. However, an important caveat to our ndings is that even when a pragmatic measure of treatment delity is identi ed, some authors have found that it is di cult for practitioners to sustain delity assessment in the longterm, unless an organizational culture is present that recognizes delity assessment as essential for optimal clinical outcomes (8). Therapist drift can occur over time, and thus, ongoing attention to delity is important well after a new treatment has been implemented and maintained.…”
Section: Discussionmentioning
confidence: 80%
“…However, assessment of delity in real-world practice settings remains challenging and has lagged behind (7). Evidence suggests that clinicians view the time and commitment required for regular delity checks too onerous in light of ever-increasing clinical and administrative demands (8). The development of delity measures that are pragmatic, e cient and reliable may help surmount these barriers.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it can be used as an organizing structure that informs the entirety or parts of a research project such as hypothesis development, measurement design, data collection, analysis, and reporting. This is visible in multiple recent studies conducted within child and family services, which describe the use of the CFIR as an implementation planning tool (Flynn et al, 2018; Henderson et al, 2017), an instrument to organize and analyze data (Marques et al, 2016; Ordway et al, 2018), and an object of research in itself in that the CFIR is examined in light of empirical research findings (Barwick et al, 2019). This latter in-depth use of the CFIR, which is aimed at advancing the framework itself as well as the discipline of implementation science, occurs less often (Kirk et al, 2016), highlighting the need to more systematically reflect on the utility and limitations of implementation frameworks and on ways to enhance them (Albers et al, 2017).…”
Section: Methodsmentioning
confidence: 99%